Gagasan Pluralisme Agama pada Kaum Teosofi Indonesia (1901-1933) - Media Zainul Bahri (Ulumuna, 2013)
This article elucidates the idea of religious pluralism among Indonesian theosophies society (MTI), an association of well-educated people of Nusantara from 1901 through 1933, whose members were dominated by the high-class of Javanese and Sumatran people, Dutch and other Europeans. It argues that MTI’s ideas about pluralistic and inclusive religious perceptions and attitudes were indeed influenced by perennialism, religious humanism, Javanese Islam and Sufism that accepted religious pluralism. MTI’s deep religious outlooks and insights resulted from mixed ideas coming from diverse socio-cultural backgrounds: Europe, America, India, China and indigenous Nusantara traditions which emphasizes the principles of harmony.